Standardized technique for single‐docking robotic rectal surgery. (October 2016) - Ahmed, J.; Siddiqi, N.; Khan, L.; Kuzu, A.; Parvaiz, A.
Abstract: Aim: The aim of this technical note is to describe our standardized technique for rectal surgery using a single‐docking totally robotic approach. Method: The data related to patients who underwent single‐docking robotic rectal surgery were analysed for the feasibility of this approach. Results: This technique was used in 124 consecutive patients who underwent rectal resection since July 2013. Male to female ratio of patients was 2:1 while median age was 67 years (range 24–92). The median operating time was 240 min (range 105–456), whilst blood loss was 10 ml (range 0–200). There was no evidence of intra‐operative complications or conversions to either a laparoscopic or an open procedure. The median length of stay was 7 days (range 3–48). Conclusion: A single‐docking technique for robotic rectal surgery is safe and feasible. It can be considered as standard approach for pelvic robotic surgery.